Strategi Kepala Sekolah Untuk Membangun Image Sekolah Yang Bermutu - Melda, Bernadeta (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to analyze the principal’s strategy in creating a quality school image. The research method uses a qualitative method. Data collection tools use interviews, documentation, observation and literature review. Data analysis uses qualitative descriptive analysis. The results of the study state that the principal’s strategy to build a quality state school image focuses on improving the quality of learning, the quality of graduates, the participation of parents, school residents and the community, and improving the quality of school facilities and infrastructure. The leading obstacle in implementing the strategy of building a quality state school image lies in the community’s assessment of the school. For this reason, efforts to improve school quality standards, especially teacher and education personnel competency development activities, must continue to be carried out so that they have an impact on high public trust.